The Influence Of Labor Migration On The Citizen Identity Of The Population (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the impact of labor migration on the civic identity of the population. The study analyzes the cultural, social, and political factors faced by labor migrants during their adaptation to a new social environment, and assesses how these factors influence their civic consciousness and sense of belonging. Special attention is given to changes in identity resulting from migration, attitudes toward national values, and issues of civic engagement. The topic is further examined through sociological research and practical examples. The findings of the study hold practical significance for migration policy, social integration, and the development of a civic society.